2019
DOI: 10.1186/s12199-019-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure to lead for Japanese children and pregnant women, estimated using duplicate food portions and house dust analyses

Abstract: BackgroundLead is a toxic metal abundant in the environment. Consumption of food contaminated at low levels of lead, especially by small children and pregnant women, raises a health concern.MethodsDuplicated food portions and drinking water were collected over 3 days from 88 children and 87 pregnant women in Shimotsuke, Tochigi, Japan. Participants were recruited in this study between January 2014 and October 2015. Dust was also collected from their homes. Lead concentrations were measured and consequent oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(64 reference statements)
2
6
0
Order By: Relevance
“…In a Japanese study (2019), the weekly Pb exposure for children aged 1–3.5 years was 3.28 ± 0.26 μg/kg BW/week. Pb concentration was higher in children than in adults, but it did not exceed the acceptable standard [ 38 ]. In another study, the content of Pb was 1.27 μg/kg BW/day, which is 35.3% of the TDI.…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese study (2019), the weekly Pb exposure for children aged 1–3.5 years was 3.28 ± 0.26 μg/kg BW/week. Pb concentration was higher in children than in adults, but it did not exceed the acceptable standard [ 38 ]. In another study, the content of Pb was 1.27 μg/kg BW/day, which is 35.3% of the TDI.…”
Section: Discussionmentioning
confidence: 99%
“…Lead exposure from other sources, such as house dust, soil, and toys, in Japan was estimated using the results of previous studies [27][28][29] . Some studies have indicated that exposure from non-dietary sources might be important in children 30,31) ; however, the estimated values of the contribution of non-dietary sources to the overall lead exposure were highly variable depending on the studies and thus no representative value could be derived.…”
Section: Exposure From Various Sourcesmentioning
confidence: 99%
“…Further exposures which may be associated with elevated BLC were not included in our analyses and may therefore give rise to residual confounding; for example, housing tenancy (owned or rented) [18,51] parental occupation [52,53], ethnicity [17], other sources of exposure, diet, contaminated land, soil quality or contaminated consumer products [6,19,20,38,41,54]. Additionally, some case characteristics used ecological proxy measures based on area (e.g., deprivation, housing age and type) which may be inaccurate, leading to misclassification.…”
Section: Limitationsmentioning
confidence: 99%
“…Children with pica are known to pick at and/or chew surfaces in the home painted with lead paint and this can be a source of lead exposure (photo courtesy of Rebecca Ingham, Advanced Health Protection Practitioner, Yorkshire and Humber Health Protection Team (HPT), UK Health Security Agency (UKHSA), 2021) paint was the source of lead concentration in dust, which was correlated with age of housing (p = 0.036) [19]. Food and house dust have also been found to be key sources of lead contamination in the home [20], along with outdoor soil [21], household dust from kitchen floors and ingress of dust indoors from outdoor sources [22]. Given the expectation that older houses and houses with gardens are more likely to contain lead in various forms, it would seem reasonable to evaluate whether there is also an association between BLC and housing age and type in the UK.…”
Section: Introductionmentioning
confidence: 99%